Karakteristik Berpikir Intuitif Siswa dalam Menyelesaikan Soal Matematika Ditinjau dari Kemampuan Matematika - Prameswari, Della Anggun; Muniri, Muniri (Lattice Journal : Journal of Mathematics Education and Applied, 2023)
In the process of solving math problems/problems, especially in the matter of relations and functions, between one student and another student must have a different mental process. Students' mathematical abilities in solving problems quickly and immediately are influenced by mental activity that is supported by intuitive thinking. Students who find it difficult to solve math problems with analytical (formal) abilities will use their intuition to help solve problems. So the purpose of this study is to describe the characteristics of students' intuitive thinking used in solving relations and function problems which are viewed from the mathematical abilities of each level of mathematical ability. Researchers use qualitative methods in this study. The results of the data analysis show that: (1) students who have high mathematical abilities in working on relations and function problems involve the characteristics of intuitive thinking globality, status theory, self-evidence, and coerciveness; (2) students who have mathematical abilities are working on relations and function problems involving the characteristics of intuitive thinking theory status, globality, and implicitness; and (3) students who have low mathematical ability in working on relations and function questions involve the characteristics of intuitive thinking extrapolativeness, self-evidence, and globality..Â Dalam proses menyelesaikan masalah/soal matematika, khususnya pada materi relasi dan fungsi, antara siswa satu dan siswa lainnya pasti memiliki proses mental yang berbeda. Kemampuan matematis siswa dalam menyelesaikan masalah dengan cepat dan segera dipengaruhi oleh aktivitas mental yang didukung oleh pemikiran intuitif. Siswa yang merasa kesulitan dalam menyelesaikan soal matematika dengan kemampuan analitis (formal) akan menggunakan intuisinya untuk membantu memecahkan masalah. Maka tujuan dari penelitian ini mendeskripsikan karakteristik berpikir intuitif dari siswa yang digunakan dalam menyelesaikan soal relasi dan fungsi yang mana ditinjau dari kemampuan matematika dari masing - masing jenjang kemampuan matematika. Peneliti menggunakan metode kualitatif dalam penelitian ini. Hasil analisis data menunjukkan bahwa: (1) siswa yang memiliki kemampuan matematika tinggi dalam mengerjakan soal relasi dan fungsi melibatkan karakteristik berpikir intuitif globality, theory status, self evidence, dan coerciveness; (2) siswa yang memiliki kemampuan matematika sedang dalam mengerjakan soal relasi dan fungsi melibatkan karakteristik berpikir intuitif theory status, globality, dan implicitness; dan (3) siswa yang memiliki kemampuan matematika rendah dalam mengerjakan soal relasi dan fungsi melibatkan karakteristik berpikir intuitif extrapolativeness, self-evidence, dan globality.